Governmental support strategies and their effects on private capital engagement in public-private partnerships - Han, Yanbing; Guo, Hai (David) (Public management review, 2024)
The ability to leverage private investment is a key selling point of infrastructure public-private partnerships (PPPs). Research has shown that to attract private capital to infrastructure projects government support is needed. However, the specific instruments of government support and their configurations remain unclear. Drawing insights from institutional theories and the public finance literature, this paper examines the government's institutional and financial tools for leveraging private capital. Based on a fuzzy-set qualitative comparative analysis of 34 road projects in the U.S. we reveal the multiple configurations of government support strategies that are consistent with high private investment.